Audit Kepatuhan Syariah Melalui Peran Dewan Pengawas Syariah Pada PT. BPRS Dana Mulia Surakarta - Fatmawati, Diah Ayu; Usnan, Usnan (JIFA (Journal of Islamic Finance and Accounting), 2018)
The aim of this study is to find out how the shariah compli- ance audit is carried out through the role of the sharia supervisory board (DPS) at PT. BPRS Dana Mulia Surakarta. This study is us- ing a qualitative approach, where the data in this study were obtained through interview, documentation and observation techniques related to the implementation of sharia compliance audits through the role of DPS in BPRS Dana Mulia Surakarta, which then obtained data analyzed descriptively. The results showed that the shariah compliance audit was im- plemented through the role of the sharia supervisory board (DPS) at PT. BPRS Dana Mulia Surakarta, it’s just that the implementation of the role of DPS in the BPRS under study is still not optimal, among others: (1) The role of DPS as a supervisor is still not optimal consid- ering there are still several products at PT. BPRS Dana Mulia Sura- karta which has not fulfilled the sharia principles. (2) The role of DPS as Advisor still needs to be improved because all this time the Sharia Supervisory Board (DPS) is only limited to providing advice from the findings of the work and providing studies to employees without any deeper follow up. Keywords: Shariah Compliance Audit and DPS JEL Classification: G21, G28,M38, M42